Current state and priorities of post-war entrepreneurship development in Ukraine - Olha Brahina; Maria Bondarchuk (CES Working Papers, 2023)
The full-scale military invasion of the Russian Federation in February 2022 caused significant damage to the Ukrainian economy. The war caused obstacles in the sphere of foreign and domestic trade, disruption of transport and logistics processes, outflow of personnel abroad or partial movement of labor resources within the country, occupation of territories, destruction, looting of enterprises, which certainly affected the ability of entrepreneurship to fully function. This made it necessary to study the impact of war on the state of entrepreneurship of Ukraine. The purpose of the article is to study the state and identify priorities for the restoration and further development of entrepreneurship in the post-war period.
Keywords: 330; trade; entrepreneurship; war; development; European Union